DAMPAK UANG SAKU TERHADAP KEINGINAN BELAJAR MATEMATIKA PADA MURID SEKOLAH DASAR - Deny Hadi Siswanto (Jurnal Lingkar Mutu Pendidikan, 2024)
This research employs symmetrical correlational methodology with the goal of investigating the potential link between the allocation of pocket money and the level of interest in mathematics learning among sixth-grade students attending Muhammadiyah Pulokadang Elementary School. A total of 30 students participated as samples in this study. Information was gathered through the administration of questionnaires and the exakeinginanion of relevant documentation. Analysis of the data entailed employing descriptive statistical techniques alongside inferential statistical methods. The results of the descriptive analysis indicate that the average score for the pocket money provision questionnaire is 59.3, indicating a good category, while the average score for the mathematics learning interest questionnaire is 66.40, which also indicates a very good category. The Pearson product-moment correlation test was conducted with a significance level set at 5%, resulting in a significance value of 0.029, which is less than 0.05. Hence, the null hypothesis was rejected. Based on these findings, it can be inferred that there exists a noteworthy and positive correlation between the provision of pocket money and the level of interest in mathematics learning among students. Additionally, this implies that offering pocket money may positively influence the degree of interest in mathematics learning among sixth-grade students attending Muhammadiyah Pulokadang Elementary School.